Platinum-nickel alloy excavated nano-multipods with hexagonal close-packed structure and superior activity towards hydrogen evolution reaction - Zhenming Cao (Nature Portfolio, 2017)
While crystal phase modification may endow materials with altered functionality, the fabrication of allomorphic noble metal nanomaterials is challenging. Here, the authors synthesize an unusual hexagonal close-packed platinum-nickel alloy and demonstrate its enhanced hydrogen evolution catalytic activity.